Mediation of Power in Political Communication in the Era of Information Globalization (Case Study of the Golkar Party) - Achmad Muchlis; Andi Faisal Bakti (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2026)
Information globalization has fundamentally transformed the structure and practice of political communication in contemporary democracies. Rapid, cross-border digital information flows mediated by global media platforms have weakened the capacity of states and political parties to control public narratives. Political communication no longer operates within centralized and hierarchical spaces, but rather within fragmented and competitive digital public spheres. This study aims to analyze how the Golkar Party, as an established political party, conducts political communication in the context of information globalization and the weakening role of the state. This research employs a qualitative approach within a constructivist paradigm using a case study design. Data were collected through in-depth interviews with local Golkar Party elites and document analysis, and analyzed using critical discourse analysis. The findings indicate that Golkar’s political communication functions as a process of mediated meaning negotiation within digital media environments. Political power is no longer derived solely from formal institutional structures, but increasingly depends on media visibility and public trust. The Golkar Party adopts a hybrid political communication strategy by combining organizational structures with adaptive digital communication practices. This study concludes that political communication of established parties in the era of information globalization should be understood as a dynamic and relational arena of mediated power, where political legitimacy is continuously negotiated within digital public spaces.